EVOLUTION AND CURRENT STATE OF UKRAINE’S INTERNATIONAL IMAGE IN THE CONTEXT OF PUBLIC GOVERNANCE AND GLOBAL COMMUNICATIONS - Denysiuk, Olga (Public Management and Policy, 2025)
The article presents a comprehensive analysis of Ukraine’s international image from 1991 to 2025, accounting for political cycles, wartime challenges, and the digital transformation of communications. The relevance of the study is determined by the radical transformation of Ukraine’s global image amid ongoing information wars, hybrid threats, and the growing role of reputational capital in public governance. The research reveals that a positive state image functions not only as a symbolic asset but also as an indicator of the effectiveness of political institutions, the transparency of communication, and the government’s ability to sustain trust during crises. The purpose of the study is to analyze the evolution of Ukraine’s national brand, identify key factors influencing its development, and substantiate an operational framework for its further enhancement. Methodologically, the paper adopts an interdisciplinary approach that integrates theories of nation branding, public and cultural diplomacy, and strategic communications. It combines content analysis of leading international media, comparative analysis of governmental and non-governmental case studies, and an indicator-based methodology drawing on the Brand Finance Global Soft Power Index, Anholt–Ipsos Nation Brands Index, FutureBrand Country Index, and Edelman Trust Barometer. The article systematizes the main stages of Ukraine’s image formation in the international information space and identifies four key periods: 1991–2003 – a phase of low recognition; 2004–2013 – the rise of a democratic image following the Orange Revolution; 2014–2021 – the consolidation of Ukraine’s reputation as a state defending freedom and European values; and from 2022 onward – the transformation of Ukraine into a symbol of resilience, bravery, and global leadership. The study demonstrates that the key determinants of positive change include public diplomacy, creative industries, volunteer initiatives, active digital communication through social media (Twitter/X, Instagram, TikTok, YouTube), and institutional collaboration between the state and civil society. The role of cultural diplomacy, educational projects, and national-patriotic practices is substantiated as a vital component of the country’s soft power. It is concluded that Ukraine’s image has evolved from a peripheral perception into a systemic factor of international positioning. Its effectiveness is ensured through the synergy of governmental, regional, and civic actors, the integration of communication into public policy, and reliance on measurable indicators of trust. The article proposes an operational model for state brand development – “policy–performance–messaging–perception–trust” – which connects institutional resilience, digital diplomacy, cultural representation, and behavioral metrics. The findings have practical significance for improving the effectiveness of state image policy, designing a unified national communication strategy, and strengthening Ukraine’s reputational resilience in the global information space.